2019
DOI: 10.1016/j.gloenvcha.2019.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Cross-site analysis of perceived ecosystem service benefits in multifunctional landscapes

Abstract: The authors acknowledge funding from the European Community's Seventh Framework Programme under Grant Agreement No.613520 (project AGFORWARD). We would like to thank the residents in all the study areas for participating in the survey. We also acknowledge the contribution of M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 92 publications
(106 reference statements)
8
67
1
1
Order By: Relevance
“…We found domestic visitors to upload more photos of recreation and social values and less scenic landscapes compared with international visitors. Similar results have been reported by Walden‐Schreiner et al (2018) and Fagerholm et al (2019). Data from PPGIS captured a higher diversity of values compared to Flickr, with domestic visitors appreciating cultural, hunting and fishing, and gathering values more than international visitors, who mapped more values related to recreation, wilderness and clean water.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found domestic visitors to upload more photos of recreation and social values and less scenic landscapes compared with international visitors. Similar results have been reported by Walden‐Schreiner et al (2018) and Fagerholm et al (2019). Data from PPGIS captured a higher diversity of values compared to Flickr, with domestic visitors appreciating cultural, hunting and fishing, and gathering values more than international visitors, who mapped more values related to recreation, wilderness and clean water.…”
Section: Discussionsupporting
confidence: 91%
“…Data from PPGIS captured a higher diversity of values compared to Flickr, with domestic visitors appreciating cultural, hunting and fishing, and gathering values more than international visitors, who mapped more values related to recreation, wilderness and clean water. The attachment of different groups of people to a place can be key to understand nature qualities that need to be managed, and to discern management actions to avoid conflicts among users (Fagerholm et al, 2019; Gundersen, Mehmetoglu, Vistad, & Andersen, 2015). The difference in mapped NCP can also be indicative of more deeply rooted cultural differences, as determined, for example, by the country one resides in Brown et al (2015).…”
Section: Discussionmentioning
confidence: 99%
“…The workflow of data collection and analysis is presented in Figure . More detailed analysis of the spatial patterns of the mapped ecosystem service benefits are reported in Fagerholm et al ().…”
Section: Methodsmentioning
confidence: 99%
“…For example, Branca et al () associated multifunctionality with climate change mitigation and poverty alleviation in Brazil; Goldstein et al () elicited how, in participatory rural development processes, increasing multifunctionality is beneficial to climate change mitigation, food security and diversification of rural economic opportunities. European studies show that multifunctional landscapes are perceived as hotspots of ecosystem services supply that provide multiple benefits and values to the well‐being of different user groups (Fagerholm et al, ; García‐Llorente et al, ; Garcia‐Martin et al, ; Plieninger, Dijks, Oteros‐Rozas, & Bieling, ).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have reported the diverging perceptions of the demand, importance, and value of ESs among different stakeholders and users (contributions 4, 10, and 11). Diverging perceptions of ESs can be caused by knowledge gaps, as identified by Paschoud et al (contribution 10), among tourists and farmers on farms in the Italian Alps or by the diverging stakeholders' demands for ESs [15] and the valuation of their benefits [16,17].…”
Section: Identified Limitationsmentioning
confidence: 99%